Adaptive capacity and ecological stability of some bean varieties in the conditions of the western forest-steppe of the Priobie region - O. V. Parkina; O. E. Yakubenko; N. T. Nguyen (Овощи России, 2024)
Relevance. Crop productivity is determined by genotype, environmental effects and their interactions. Comprehensive evaluation of crop varieties based on their adaptability, plasticity and stability makes it possible to select the most promising varieties, high-yielding and adapted to many environmental conditions to improve productivity.Materials and Methods. Fourteen common bean varieties were tested in a randomized complete block design with three replications during two years (2022 and 2023) in the experimental field “Michurintsev Garden” of Novosibirsk State Agrarian University. Productivity traits were taken into account: number and weight of beans per plant, weight of 1000 seeds, yield. The purpose of the work was to evaluate bean samples for adaptive capacity and ecological stability in the conditions of the forest-steppe Priobie.Results. The article provides an assessment of the adaptability and stability of bean varieties in order to identify varieties with high productivity and adapted to climatic and farming conditions in the Siberian region. The results of the tests showed that the highest average net yields of Rubin, Krasnopestraya, Zolotistaya and Muhranula varieties were in the range of 0.41-0.64 kg/m2. Analysis of genotype-environment interaction (GxE) according to the mathematical model of Eberhart and Russel shows that varieties Rubin, Krasnopestraya, Zolotistaya and Muhranula have high indices of general adaptability and breeding value of genotype, Among them, varieties Rubin and Zolotistaya have stable productivity and high adaptability to environmental conditions.